KUALITAS AIR SUNGAI PITAP BERDASARKAN INDEKS AUTOTROPIK DI KALIMANTAN SELATAN - Sasi Gendro Sari; Siti Hanna Aprida (Universitas Lambung Mangkurat, 2018)
An epilithic benthic algae functions as a primary producer living on rock substrates. The Autotrofic Index (AI) was measured to understand the level of water pollutions by quantifying an autotrofy organism. This research determined water quality of Pitap river based on the autotrofic level of an epilithic benthic algae and to understand the correlation between the autotrofic level and physicochemical parameters. The measurement of water quality based on Ash-Free Dry Mass (AFDM), the amount of chlorophyll-a and physicochemical parameters were taken every month with two repetitions on September and October 2014. Five sampling sites were selected using a purposive sampling method based on the variety of environmental conditions around the Pitap river. The results showed that the water quality in the upstream (Ajung and Langkap villages) were classified non-pollution (dominated by autotrof compounds) until less pollution (dominated by autotrof-heterotof compounds). Other locations in downstream (Tebing Tinggi, Sungsum and Juuh villages) were determined pollution of water quality by dominance of autotrof-heterotrof components to dominance by heterotof components. Spearman correlation explained that autotrofic index on September 2014 was closely correlated with water temperature and water velocity with their value are 0,954 and -0,794 at significantly α=0,01. On October 2014 water temperature was closely correlated with its value 0,681 at significantly α=0,05.